Effect of the Central Canal in the Spinal Cord on Fluid Movement within the Cord. Issue 5 (October 2013) - Drøsdal, Ida N.; Mardal, Kent-Andre; Støverud, Karen; Haughton, Victor
Computational studies are used to demonstrate the effect of oscillating CSF flow on pressures within the spinal cord. We tested the hypothesis that the central canal in the spinal cord affects spinal cord pressure gradients resulting from oscillatory CSF flow. Two computational models of the spinal cord were created with the same dimensions. Model 1 had a homogeneous porous structure. Model 2 had the same structure with the addition of a central fluid filled space, representing the central canal of the cord. We simulated oscillatory flow in the fluid space using standard computational fluid dynamics tools. For all phases of the CSF flow cycle and for specific projections through the model we calculated pressure gradients and fluid movement in the cord models. Pressures in the models varied through the flow cycle. Model 1 had linearly varying pressure along its long axis that varied with the cycle and had no pressure gradients across the cord. Model 2 had nonlinear varying pressure along its long axis varying with the time in the cycle and had transient centrifugal and centripetal pressure gradients with a central fluid space. The radial pressures varied linearly with distance from the fluid space. Centrifugal and centripetal pressure gradients resulted in radially directed fluid flow in the cord. The central canal within the spinal cord alters the pressure fields occurring during oscillatory CSF flow and creates centrifugal and centripetal fluid flux in the cord.